2019
DOI: 10.1002/ejoc.201900105
|View full text |Cite
|
Sign up to set email alerts
|

Direct, Microwave‐Assisted Synthesis of Isothiocyanates

Abstract: A microwave‐assisted desulfuration of readily available dithiocarbamates, formed in situ from primary amines, leading to target isothiocyanates has been developed. This efficient protocol provides a rapid, environmentally benign route to aliphatic and aromatic isothiocyanates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…Comparing the yields of aliphatic ITCs obtained in optimal conditions in Method A with previous results using only microwave radiation to synthesis of aliphatic ITCs [ 63 ], it can be concluded that application of DMT/NMM/TsO − ( 1 ) as a desulfurating agent allows us to receive the final isothiocyanates 4a–i with higher yield. The biggest yield difference was found for ITC 4f (72% vs. 50% [ 63 ]), and the smallest for ITC 4i (83% vs. 82% [ 63 ]). For other ITCs, except 4j , which was not previous obtained, the yields were higher, from 5 to 14%, than in previous publication [ 66 ].…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Comparing the yields of aliphatic ITCs obtained in optimal conditions in Method A with previous results using only microwave radiation to synthesis of aliphatic ITCs [ 63 ], it can be concluded that application of DMT/NMM/TsO − ( 1 ) as a desulfurating agent allows us to receive the final isothiocyanates 4a–i with higher yield. The biggest yield difference was found for ITC 4f (72% vs. 50% [ 63 ]), and the smallest for ITC 4i (83% vs. 82% [ 63 ]). For other ITCs, except 4j , which was not previous obtained, the yields were higher, from 5 to 14%, than in previous publication [ 66 ].…”
Section: Resultssupporting
confidence: 51%
“…in the presence of triethylamine (Et 3 N) (4 equiv.) in DCM as the solvent enabled formation of intermediate dithiocarbamate 3a in just 5 min at room temperature (rt) [ 63 ]. The obtained dithiocarbamate 3a was subjected to a microwave-assisted reaction with 1 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Commonly, they are synthesized by using thionyl transfer agents (thiophosgene, its derivatives, 2,[44][45][46][47][48] or, more recently, uorinated agents) [49][50][51][52][53][54] or via the formation of dithiocarbamate salts with carbon disulde under basic conditions, followed by desulfurization (Scheme 1a). 44,[55][56][57] These approaches are usually chosen due to the easy access of the respective amines, which can be transferred quickly to the ITC in one or two steps. However, these reagents are highly toxic (thiophosgene and carbon disulde, the latter additionally being volatile) and their synthesis typically involves noxious compounds (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This work has two main aims: (i) to replace the commonly used 3,5-bis(trifluoromethyl) phenyl motifs by surrogates that perform similarly or exhibit improved catalytic activity and furthermore (ii) to introduce a new and simplified synthesis strategy for thiourea catalysts. Thus, in contrast to the typically applied thiourea catalysts synthesis routes involving thiophosgene, [40][41][42] its surrogates [34,[43][44][45][46][47] or other toxic compounds, [48,49] a multicomponent reaction (MCR) approach is investigated herein in order to decrease the overall toxicological impact and at the same time provide a straightforward and structurally versatile access to the desired catalysts. Our approach is based on a report by Al-Mourabit et al, [50] who extended the synthesis protocol of Lipp et al [51] and reported the synthesis of thioureas from aliphatic amines, isocyanides and elemental sulfur in excellent yields at ambient to moderate temperature.…”
Section: Introductionmentioning
confidence: 99%